Achieving Success in the Indian Handcrafted Furniture Industry through Export-Orientation and Challenges Confronted. - BALDWA, SOURABH (2009)
This research sheds light upon various characteristics of SMEs and their distinctive behavioural patterns in the process of exporting and managing their resources. The case for Indian handcrafted furniture-manufacturing industry of Jodhpur, in the state of Rajasthan is used for the purpose of research. The primary aim of my research is to determine the exporting behaviour and difficulties faced for exporting and lack of awareness for exporting and lastly the success factors to be considered in order to enhance the handicraft segment of Indian industries. Based on observation and experiments a primary research was conducted which includes an extensive search and critical evaluation of previously written literature which focussed on SMEs and difficulties they faced in exporting, and based on the literature with cited theories purposeful strategies are construed.